Colorimetric determination of Salmonella typhimurium based on aptamer recognition. Issue 35 (25th August 2016) - Zhu, Changqing; Hong, Ying; Xiao, Zhen; Zhou, Yang; Jiang, Yuan; Huang, Ming; Xu, Xinglian; Zhou, Guanghong
Abstract : A sensitive colorimetric detection of S. typhimurium based on aptamer recognition with a detection limit of 10 cfu mL −1 . Abstract : A sensitive method for the colorimetric determination of Salmonella typhimurium ( S. typhimurium ) was developed based on aptamer recognition and gold nanoparticles. First, a biotinylated specific aptamer for S. typhimurium was immobilized on avidin-coated microplate wells. Then, target bacteria, a biotinylated aptamer and avidin-catalase were successively introduced into the microplate wells. Finally, hydrogen peroxide and freshly prepared gold(iii ) chloride trihydrate were added, and the absorbance of the reaction product was measured with a plate reader. Under optimized conditions, there was a linear relationship between the absorbance (A550 nm) and the concentration of S. typhimurium over the range of 10 1 to 10 6 cfu mL −1 ( R 2 = 0.9920), with a detection limit of 10 cfu mL −1 . This simple rapid method provided a promising tool for on-site screening of S. typhimurium in raw chicken samples.